Study of Hidden Curriculum As a Method of Non-Formal Education in Islamic Boarding Schools - Latif, Muhammad Sabri; Tharaba, M. Fahim; Susilawati, Samsul; Mutniati, Vebri Putri; Mu’in, Mohammad Lutfi Alil; Munawaroh, Aminatul (Journal of Instructional and Development Researches, 2025)
This research examines the role of the hidden curriculum as a non-formal education method in shaping the Islamic character of students in Islamic boarding schools. The hidden curriculum includes values, norms and habits that are implicitly instilled through interactions, culture and daily routines of Islamic boarding schools, such as the implementation of worship, the habit of discipline, responsibility and independence. This research uses a library research method to analyze theory, practice and challenges in implementing the hidden curriculum. The research results show that the hidden curriculum contributes significantly to the formation of the moral, spiritual and social dimensions of students, although they still face challenges such as a lack of conceptual understanding, the dominance of the formal curriculum and minimal evaluation. Optimizing the hidden curriculum requires strategic management, such as training for Islamic boarding school managers, integration with the formal curriculum, example by caregivers, and regular evaluation. With planned and systematic management, the hidden curriculum has great potential to support the creation of holistic education in Islamic boarding schools, which not only produces intellectually intelligent students, but also has strong Islamic character and is adaptive to the challenges of the times.